NO SURRENDER : FAITH, FAMILY, AND FINDING YOUR WAY - Bisher, Patrick; Land, Jon (Post Hill Press, 2017)
Patrick Bisher’s career as a Navy SEAL should have ended after a parachuting accident nearly crippled him. But overcoming adversity, even an injury as serious as a broken hip, was nothing new for him. He’d spent a portion of his childhood in leg braces. Doctors told him he’d never walk again thanks to a degenerative hip condition. He wasn’t about to give up then, any more than he was in the wake of that parachute training accident. Instead, he went on to serve in combat as a member of SEAL Team Seven, seeing action in Iraq and ultimately winning the Army Commendations Medal, among other awards. Now Patrick wants to take the lessons he learned on and off the battlefield and apply them to everyday life. He offers inspiration to all who’ve faced the kind of adversity he has. In chapters drawn directly from his own experience, he sketches a heart-wrenching tale of salvaging lifelong victories out of crushing defeats, and hope out of heartache.